1999
DOI: 10.1046/j.1365-2516.1999.t01-1-00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal DDAVP induced increases in plasma von Willebrand factor alter the pharmacokinetics of high‐purity factor VIII concentrates in severe haemophilia A patients

Abstract: Because native circulating factor VIII (FVIII) is maximally stabilized when it is bound to von Willebrand factor (vWf), increased plasma vWf levels may enhance the infused FVIII concentrate intravascular survival and efficacy in severe haemophiliacs. To assess whether the kinetic characteristics and recovery of high purity, plasma-derived (Monoclate-P, Centeon) and recombinant (Bioclate , Centeon) FVIII concentrates are enhanced by increased plasma vWf concentrations, we compared the pharmacokinetic response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…39 In addition, Deitcher et al have shown that volume of distribution increases after desmopressin administration, which, of course, results in an overall increase in VWF levels. 40 Moreover, we believe that VWF may play a crucial role in the perioperative setting with regard to FVIII PK parameters, as previous studies have demonstrated a clear association between VWF plasma concentrations and FVIII halflife. 41,42 This is not surprising, as VWF protects FVIII against proteolytic degradation by expression of ABH antigens on N-linked glycans and the uptake of the copper-binding protein ceruloplasmin.…”
Section: A B C Dmentioning
confidence: 79%
“…39 In addition, Deitcher et al have shown that volume of distribution increases after desmopressin administration, which, of course, results in an overall increase in VWF levels. 40 Moreover, we believe that VWF may play a crucial role in the perioperative setting with regard to FVIII PK parameters, as previous studies have demonstrated a clear association between VWF plasma concentrations and FVIII halflife. 41,42 This is not surprising, as VWF protects FVIII against proteolytic degradation by expression of ABH antigens on N-linked glycans and the uptake of the copper-binding protein ceruloplasmin.…”
Section: A B C Dmentioning
confidence: 79%
“…by inhibiting the binding of activated PC to FVIII [30]. Interestingly, in previous studies it has not been possible to prolong FVIII halflife in patients with haemophilia A by the infusion of desmopressin, which leads to an increase of plasma VWF [28,31]. It is important to mention that also the half-life of the novel FVIII concentrates with prolonged half-life is associated with VWF levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, human studies have shown that DDAVP administration can significantly increase endogenous plasma VWF:Ag levels in PWH. However, DDAVP pre‐treatment 2 hours prior to infusion of FVIII had no significant effect on FVIII clearance 49 …”
Section: Inter‐individual Variations In Vwf Clearance Pathwaysmentioning
confidence: 91%